Citizen science at the roots and as the future of forensic genetic genealogy - Granja, Rafaela (International journal of police science & management, 2023)
Forensic genetic genealogy is an emergent forensic technology that employs databases used by citizens to upload genetic data voluntarily to search for criminal suspects and/or unidentified individuals. Considering a wide view of the roots of forensic genetic genealogy, in this article, I draw on publicly available interviews with key stakeholders in the field, media articles, and companies’ statements to analyze how this technology is both grounded and based upon citizen science. That is, a type of science to which citizens actively, voluntarily, and consentingly contribute in various forms. On the one hand, I show how the emergence of forensic genetic genealogy is mainly based upon the work of individuals with a personal interest in genetic genealogy, who are heavily invested in constructing their own and others’ family trees. That is, citizens from various educational backgrounds and professional activities who became an untapped source of valuable expertise for forensic science because of their prolific experience in conducting genetic genealogy. On the other hand, I argue that the current situation of forensic genetic genealogy is also highly dependent on citizens’ interest and willingness to upload genetic data into publicly accessible genealogy databases and voluntarily deciding to make them available to law enforcement searches. Perceiving citizen science as being at the roots and as the future of forensic genetic genealogy has important implications for the forensic epistemic culture and the protection of citizens’ rights that must be considered in the development and implementation of such technology.